A Contemporary Assessment of Acute Mechanical Ventilation in Beijing: Description, Costs, and Outcomes. Issue 7 (July 2017) - Ye, Yanping; Zhu, Bo; Jiang, Li; Jiang, Qi; Wang, Meiping; Hua, Lin; Xi, Xiuming
Abstract : Objective: To evaluate the contemporary practice, outcomes, and costs related to mechanical ventilation among ICUs in China. Design: A prospective observational cohort study. Setting: Fourteen ICUs among 13 hospitals in Beijing, China. Patients: Seven hundred ninety-three patients who received at least 24 hours of mechanical ventilation within the first 48 hours of ICU stay. Intervention: None. Measurements and results: The mean age was 64 years. Sixty-three percent were male. New acute respiratory failure accounted for 85.5% of mechanical ventilation cases. Only 4.7% of the patients received mechanical ventilation for acute exacerbation of chronic obstructive pulmonary disease. The most widely used ventilation mode was the combination of synchronized intermittent mandatory ventilation and pressure support (43.6%). Use of lung-protective ventilation is widespread with tidal volumes of 7.1 mL/kg (2.1 mL/kg). The ICU/hospital mortality was 27.6%/29.3%, respectively (8.5%/9.7% for surgical patients and 41.3%/43.2% for medical patients, respectively). The mean level of ICU/hospital cost per patient was $15, 271 (18, 940)/$22, 946 (25, 575), respectively. The mean daily ICU cost per patient was $1, 212. Conclusion: For the first time, we obtained a preliminary epidemiology data of mechanical ventilation in Beijing, China, through the study. Compared with the other nations, our patients are older, predominantly male, and treated according to prevailing international guidelines yet at a relatively high cost and high mortality. The expanding elderly population predicts increase demand for mechanical ventilation that must be met by continuous improvement in quality and efficiency of critical care services. Abstract : Supplemental Digital Content is available in the text.